Social computing in digital education : first International Workshop, SOCIALEDU 2015, Stanford, CA, USA, August 19, 2015, Revised selected papers /: first International Workshop, SOCIALEDU 2015, Stanford, CA, USA, August 19, 2015, Revised selected papers. (2016) - Unknown
No abstract available